Infrared Analysis of Dust Temperature and Mass Around PSR J0407+16 Using IRIS 60 and 100µm Data - Adhikari, Arun; Upadhya Dhakal, Nabin; Kunwar, Manjeet; Bhusal, Nabin; Khatiwada, Manil; Paudel , Rajendra (BMC Journal of Scientific Research, 2025)
We examine the physical properties of a localized interstellar dust structure in the vicinity of the millisecond pulsar PSR J0407+16 using archival far-infrared data from the Improved Reprocessingof the IRAS Survey (IRIS) at 60 and 100 µm. Infrared flux maps were extracted from FITS images using Aladin v2.5, and pixel-by-pixel analyses were carried out with Python. The 60/100 µm flux ratio was used to calculate dust colour temperatures under the assumption of optically thin emission and a fixed dust emissivity index (β = 2). A modified blackbody approach was used to estimate dust masses. Using a Gaia EDR3 distance of 200 pc, the dust temperature was found to fluctuate within a narrow range of 21.42–22.64 K, with a mean value of 22.05 K. 1.57–2.08 MJy sr⁻¹ at 60 µm and 10.77–11.78 MJysr⁻¹ at 100 µm are the equivalent flux densities. The overall dust mass of the building is determined to be 1.37 × 10²⁸ kg (≈0.007 M⊙), indicating a gas mass of 2.74 × 10³⁰ kg (≈1.44 M⊙) for a gas to-dust ratio of 100:1. Spatial variations in flux, temperature, and mass show mild asymmetries, and an inverse temperature mass relation (R² = 0.86) suggests a thermally stable dust environment close to local thermodynamic equilibrium. These results demonstrate how effectively weak, quiescent dust forms in the interstellar medium may be probed using archival infrared data.